1999
DOI: 10.1074/jbc.274.40.28724
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of cDNA Encoding Cardosin A, an RGD-containing Plant Aspartic Proteinase

Abstract: Cardosin A is an abundant aspartic proteinase from pistils of Cynara cardunculus L. whose milk-clotting activity has been exploited for the manufacture of cheese. Here we report the cloning and characterization of cardosin A cDNA. The deduced amino acid sequence contains the conserved features of plant aspartic proteinases, including the plant-specific insertion (PSI), and revealed the presence of an Arg-Gly-Asp (RGD) motif, which is known to function in cell surface receptor binding by extracellular proteins.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
1
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(88 citation statements)
references
References 40 publications
2
80
1
3
Order By: Relevance
“…Finally, the 80 kDa plasma membrane protein is an RGD binding protein capable of strong selectivity towards the RGD sequence. Only few RGD dependent protein-protein interactions have been described in plants [27][28], and their involvement in cell wall-membrane attachments remains to be elucidated. In contrast, the wall-associated kinases (WAKs) are bound to both the plasma membrane and the extracellular matrix [29], but these links are not mediated by an RGD sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the 80 kDa plasma membrane protein is an RGD binding protein capable of strong selectivity towards the RGD sequence. Only few RGD dependent protein-protein interactions have been described in plants [27][28], and their involvement in cell wall-membrane attachments remains to be elucidated. In contrast, the wall-associated kinases (WAKs) are bound to both the plasma membrane and the extracellular matrix [29], but these links are not mediated by an RGD sequence.…”
Section: Discussionmentioning
confidence: 99%
“…The expression vector pET-23a (Novagen, Madison, WI) containing the procardosin A cDNA (pET_pCAϩPSI) has been previously constructed in our lab (14), as well as the PSI deleted procardosin A construct (pET_pCA⌬PSI) (8). The Escherichia coli BL21(DE3) strain was pur-* The costs of publication of this article were defrayed in part by the payment of page charges.…”
Section: Methodsmentioning
confidence: 99%
“…Upon incubation with carboxypeptidases, both fragments (m/z 1233.68 and 1396.73) started to shift and formed the same ladder (VS(R/Y)). This indicated that both fragments were the same C-terminal peptide with a ragged C terminus R/Y (⌬m ϭ 163.06 Da) being produced by cleavage of the peptide bonds at Tyr 13 -Gly 14 and Arg…”
Section: Expression Purification and Characterization Of Recombinanmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardosin A is a glycosylated aspartic protease (AP) that has been studied in detail and was shown to be similar to chymosin, in terms of kinetic parameters and specificity, by cleaving the same peptide bond (Phe105-Met106) of the casein kappa [7,8]. The most abundant proteolytic activity corresponds to that of cardosin A [9] and at acidic pH, it represents from 75 to 90 % of total extracted enzyme activity [8]. The second aspartic protease studied was cardosin B, which is similar to pepsin, in terms of activity and specificity [7].…”
Section: Introductionmentioning
confidence: 99%